STRATEGIC DIVERGENCE IN AUTOMOTIVE SUPPLY CHAINS: TESLA AND CHERY - Hua, Zhang; Wei, Yu; Saptari, Adi; Hanafiah, Hally; Fuadi, Muhammad Hafidz Fazli Md (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
In today's interconnected world, global supply chains play a critical role in the production and distribution of goods and services. The globalization of supply chains has been driven by the pursuit of cost efficiencies, access to new markets, and the ability to leverage specialized capabilities from different regions. This paper presents a comparative analysis of the global supply chain strategies of Tesla and Chery, focusingon the critical factors that contribute to their success or potential failure. The method used in this study is qualitative, numerous of articles published in this topic were selected from 2014 to 2023. The investigation on key aspects such as supply chain design, sourcing strategy, production strategy, inventory management, and delivery methods to highlight the distinct approaches adopted by each company. Tesla’s supply chain is characterized by vertical integration, which grants extensive control over the production process and fosters innovation. In contrast, Chery employs a more traditional and flexible supply chain strategy, relying on partnerships and outsourcing. The analysis evaluates efficiency and scalability, cost management, quality control, risk management, and customer satisfaction as primary criteria. The results indicate that Tesla’s strategies demonstrate a commitment to control and efficiency, while Chery emphasizes flexibility and cost management. By comparing these two automakers, this paper offers insights into how different supply chain strategies can impact overall success in the competitive global automotive industry.